Visualization of hypoxia in cancer cells from effusions in animals and cancer patients - Yue Li; Yue Li; Yue Li; Long Zhao; Long Zhao; Yunlong Huo; Xianghong Yang; Yong Li; Hao Xu; Xiao-Feng Li; Xiao-Feng Li; Xiao-Feng Li (Frontiers in Oncology, 2022)
ObjectiveTumor hypoxia is frequently observed in primary solid malignancies, but the hypoxic status of tumor cells floating in body cavity effusions is largely unknown, especially in patients. This study was to observe the hypoxia and proliferation status of cancer cells floating in effusions in mice and patients.MethodsThe distribution of hypoxia in cancer cells floating in ascites was first studied in nude mice. Hypoxia was detected by immunofluorescent visualization of pimonidazole and GLUT-1. For cancer patients, we retrospectively collected 21 ascites and 7 pleural effusion sample blocks of cancer patients, which were confirmed to contain tumor cells. Immunohistochemistry was performed to detect the expression of endogenous hypoxic markers HIF-1α and GLUT-1, proliferation index Ki-67. 18F-FDG PET/CT was performed to detect the glucose metabolism status of tumor cells in effusions.ResultsThe tumor cells collected from ascites were positive for pimonidazole and GLUT-1, which suggesting that the cancer cells floating in ascites were hypoxic. Patterns of tumor hypoxia in human patients are similar to those observed in animal. HIF-1α and GLUT-1 were expressed by tumor cells in nearly all 28 cytological cases. For Ki-67 index, ascites tumor cells had a relatively low expression level compared with their corresponding primary or its metastatic lesions. Tumor cells in effusions showed high 18F-FDG uptake indicated the enhanced activity of glucose metabolism.ConclusionTumor cells in body cavity effusions, as a unique subgroup of tumor, are in a state of hypoxia and low proliferation, which would be one of the driven causes of chemo-radiotherapy resistance. Novel therapeutic interventions are urgently needed to overcome tumor hypoxia.